2013
DOI: 10.1182/blood-2012-09-458752
|View full text |Cite
|
Sign up to set email alerts
|

KIR2DS1-dependent acquisition of CCR7 and migratory properties by human NK cells interacting with allogeneic HLA-C2+ DCs or T-cell blasts

Abstract: Key Points CCR7 uptake by NK cells can be strongly induced by major histocompatibility complex–specific activating KIRs, in particular by KIR2DS1 (specific for HLA-C2). The KIR2DS1-induced CCR7 expression on NK cells may expand greatly the contingent of alloreactive NK cells migrating to secondary lymphoid compartments after hematopoietic stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…Trogocytosis of target cell molecules can lead to enhanced or sustained intracellular signaling pathways and induce de novo functional properties in receiving cells. Through acquisition and incorporation of target cell proteins in the cell membrane, the receiving cells can obtain new opportunities for interaction with other immune cell types for which ligands or receptors were previously not expressed (26,36). Through the acquisition of HLA-G and possible other EVT membrane-associated molecules, the fraction of dNK with surface HLA-G may gain the ability to interact with other decidua-resident immune cells such as decidual T cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trogocytosis of target cell molecules can lead to enhanced or sustained intracellular signaling pathways and induce de novo functional properties in receiving cells. Through acquisition and incorporation of target cell proteins in the cell membrane, the receiving cells can obtain new opportunities for interaction with other immune cell types for which ligands or receptors were previously not expressed (26,36). Through the acquisition of HLA-G and possible other EVT membrane-associated molecules, the fraction of dNK with surface HLA-G may gain the ability to interact with other decidua-resident immune cells such as decidual T cells and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that KIR2DS1 facilitated trogocytosis of HLA-C2 molecules and associated membrane fragments from antigen presenting cells (APC) by pNK (26). A protective effect of the KIR2DS1 gene in the development of pregnancy complications was demonstrated (27).…”
Section: Kir2dl4-and Kir2ds1-expressing Dnk Have Increased Levels Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 KIR2DL2 and KIR2DL3 recognize HLA molecules in the HLA-C1 group, whereas KIR2DL1 and the activating KIR2DS1 receptors recognize the HLA-C2 group. 9,10 To become functional, NK cells must undergo a continuous process of "education" or "licensing." [11][12][13] This phenomenon is achieved when inhibitory KIRs interact with their cognate ligand (eg, KIR2DL2 with an HLA-C molecule in the C1 group) during development.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Among the non-HLA-specific triggering receptors, NKp46, NKp30, NKp44 (collectively termed natural cytotoxicity receptors [NCRs]), 22 NKG2D, 29 DNAX accessory molecule-1 (DNAM-1; CD226), 26 and CD16 play a major role in NK cell activation. In addition, human NK cells can express HLA class I-specific activating receptors, including KIR2DS1, 30,31 KIR2DS4,32,33 and CD94/NKG2C. 26 Two main NK cell subsets characterized by distinct phenotypic and functional properties have been described, namely the CD56 bright CD16 2/low and CD56 dim CD16 1 subsets.…”
mentioning
confidence: 99%